XRF-scanning elemental data and core descriptions from sediment cores obtained southwest off the Cabo Verde archipelago - Irene Pérez-Rodríguez; Dirk Nürnberg; Julie Schindlbeck-Belo; Jack Wharton; Thor H Hansteen; Veerle A I Huvenne; David J R Thornalley; Ángela Mosquera Giménez; Steffen Kutterolf; Kelsey Archer Barnhill; Covadonga Orejas (PANGAEA, 2024)
Semi-quantitative elemental concentrations from X-ray fluorescence (XRF) scans were measured for six sediment cores obtained during the iMirabilis2 expedition off Cabo Verde. The analyses were conducted using an Avaatech XRF core scanner at the Institute of Geosciences, Christian-Albrechts-University, Kiel University. The sediment from the core halves was smoothed with a spatula to create an even scanning surface, which was then covered with a thin film foil to prevent contamination. The resolution was set to 0.5 cm. The elements Mg, Al, Si, S, Cl, K, Ca, Ti, Mn, Fe, Co, Cu and Zn were analysed with the 10-kV setting (200 μA, 10s acquisition time, no filter) and the elements Br, Rb, Sr, Zr and Pb were analysed with the 30-kV setting (1000 μA, 20s acquisition time, Pd-thick filter). Raw X-ray spectra were converted into area counts using the iterative least-square software package WIN_AXIL from Canberra Eurisys. Elements that yielded negative area values are excluded. extquotesingleKa extquotesingle and extquotesingleLa extquotesingle after the element denote the energy state of the electrons being measured in the atom, with level extquotesingleKa extquotesingle being closest to the nucleus with the lowest energy state, while level extquotesingleLa extquotesingle is farther from the nucleus and has a higher energy state. Units are reported as area counts per second for the spectral peaks of each element, alongside chi-squares and standard deviations from the models. Additionally, pictures and lithological descriptions of the six cores are included.